KETERAMPILAN MANAJERIAL KEPALA SEKOLAH TERHADAP KOMITMEN KERJA GURU SMK - Rahmawati, Ima; Nur Aida, Siti; Lestari, Hana; Ihsan, Muzhir (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to analyze the influence of school principals' managerial skills on teachers' work commitment in vocational high schools (SMK) accredited with a